The effect of lemon extract (Citrus limon) on the blood sugar levels and pancreatic beta cell regeneration in alloxan-induced hyperglycemic mice - Petrus Mantur; Efrisca Meliyuita Br. Damanik; Elisabeth Levina Sari Setianingrum; Prisca Pakan (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: High blood sugar levels that exceed normal limits or commonly refered to as hyperglycemia, is an early symptom of diabetes mellitus. Objectives: This study explored the effect of lemon (Citrus limon) extract on blood sugar levels and pancreatic b cell regeneration in alloxan-induced hyperglycemic mice (Mus musculus). Method: This research is an experimental study using a post-test group. The sampling was carried out using a randomization method. By administering 125 mg/kg BW of alloxan, the sample was conditioned for hyperglycemia. The samples were divided into five groups: normal control, alloxan-induced control, and three treatment groups that received lemon extract with dosages of 100 mg/kg BW, 300 mg/kg BW and 500 mg/kg BW, respectively. Semiquantitative analysis was used to evaluate pancreatic damage. Results: The results showed that lemon extract can decrease blood sugar levels. Histopathological imaging revealed a significant improvement in b cell distribution and decreased vacuolization in the Langerhans islets of mice administered lemon extract. No significant differences were observed among different dosages of lemon extract (p>0.05). Conclusion: Our findings underscore the potential therapeutic benefits of lemon extract in managing blood sugar levels and promoting pancreatic b cell regeneration in alloxan-induced mice.